Maternal Theology: A Phenomenological Interpretative Analysis of the Dual Role of Mothers as Church Ministers in the Parish of Santo Yusup Gedangan - Atanasius Deimen Wahana Utama; Felisitas Verena Ardhini; Melania Dian Ayu Puspita; Fr. Wuriningsih (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2025)
This study is motivated by the dilemma faced by Catholic mothers who play dual roles as pillars of their families and formal servants in their parishes. Although the Apostolic Exhortation Familiaris Consortio affirms the family as the domestic church, the integration of domestic and public vocations often causes theological and practical tensions. The purpose of this study is to phenomenologically explore these women's experiences in integrating their roles, understand the internal conflicts that arise, and discover the sources of their resilience. Using a qualitative approach and Interpretative Phenomenological Analysis (IPA) methodology, data were collected through in-depth interviews with four women ministers (catechists/pro-deacons) at St. Joseph Parish in Gedangan. The findings reveal that role integration is achieved through scheduling strategies and the fair division of domestic responsibilities. Inner conflict is mainly experienced by mothers with young children or single parents, which is compounded by “structural sin” in the form of patriarchal expectations and exploitative ministry practices. Their perseverance is based on the experience of "finite grace" manifested through family support and community solidarity. This study concludes that the struggles of female ministers constitute an embodied theology, in which spirituality is shaped by everyday limitations. As a result, the Church is encouraged to develop gender-sensitive pastoral policies and support relational justice within families, so that mothers' vocations both at home and in the community can be integrated in a joyful and liberating way.